Zooming in on size distribution patterns underlying species coexistence in Baltic Sea phytoplankton. (16th July 2014) - Downing, A. S.; Hajdu, S.; Hjerne, O.; Otto, S. A.; Blenckner, T.; Larsson, U.; Winder, M.; Grover, James
Abstract Scale is a key to determining which processes drive community structure. We analyse size distributions of phytoplankton to determine time scales at which we can observe either fixed environmental characteristics underlying communities structure or competition‐driven size distributions. Using multiple statistical tests, we characterise size distributions of phytoplankton from 20‐year time series in two sites of the Baltic Sea. At large temporal scales (5–20 years), size distributions are unimodal, indicating that fundamental barriers to existence are here subtler than in other systems. Frequency distributions of the average size of the species weighted by biovolume are multimodal over large time scales, although this is the product of often unimodal short‐term (<1 year) patterns. Our study represents a much‐needed structured, high‐resolution analysis of phytoplankton size distributions, revealing that short‐term analyses are necessary to determine if, and how, competition shapes them. Our results provide a stepping‐stone on which to further investigate the intricacies of competition and coexistence.